Binary Boys: Autism, Aspie Supremacy and Post/Humanist Normativity - de Hooge, Anna N. (Disability Studies Quarterly, 2019)
Employing an epistemology of situated knowledges, I analyze Aspie (from: Asperger's) supremacy. This ideology consists of an interplay between anti-autistic ableism, and the frame of the Aspie subject as superior, both to other autistics and to non-autistics. This superiority is defined in terms of whiteness, masculinity and economic worthiness. I link this ideology to recent research into the collaboration of Hans Asperger with a Nazi program that involved the killing of disabled individuals. I also discuss contemporary (media) manifestations of Aspie supremacy. Furthermore, I draw a parallel between this ideology and a Lyotardian postmodernism. This type of postmodernism has been criticized for its inability to justify itself on its own terms. Through analyzing Aspie supremacy, I work through this paradox, as it relates to posthumanism.